DOI: 10.5479/ads/bib/2012ivoa.spec.0210t
|View full text |Cite
|
Sign up to set email alerts
|

Simple Spectral Access Protocol Version 1.1

Abstract: The Simple Spectral Access (SSA) Protocol (SSAP) defines a uniform interface to remotely discover and access one-dimensional spectra. SSA is a member of an integrated family of Status of This Document This document has been produced by the IVOA Data Access Layer Working Group. It has been reviewed by IVOA Members and other interested parties, and has been endorsed by the IVOA Executive Committee as an IVOA Recommendation. It is a stable document and may be used as reference material or cited as a normative ref… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…TAP may fail to warrant effective searches in reasonable time. In these cases, dedicated services with predefined search criteria like SSA (Doug et al, 2012), SIAv2, are able to focus on optimized criteria and discover the data of interest in more efficient way.…”
Section: Discussionmentioning
confidence: 99%
“…TAP may fail to warrant effective searches in reasonable time. In these cases, dedicated services with predefined search criteria like SSA (Doug et al, 2012), SIAv2, are able to focus on optimized criteria and discover the data of interest in more efficient way.…”
Section: Discussionmentioning
confidence: 99%
“…Using the technology of Virtual Observatory, namely the combination of Table Access (Nandrekar-Heinis et al 2014) and Simple Spectra Access (Tody et al 2012) protocols we have identified less than ten objects (e.g. BT CMi or HD53416) observed both by Ondřejov 2m Perek Telescope and LAMOST.…”
Section: Cross-matching and Labelling Of Lamost And Ccd700 Archivesmentioning
confidence: 97%
“…While this has not been missed for simple types (e.g., text vs. integer vs. float), violation of constraints imposed by controlled vocabularies has been an issue. As an instructive example, consider SSAP's creation type, which has to contain one of seven keywords, some of which are long and mixed case, like "spec-tralExtraction", as specified in Tody et al (2012). Weighing the increased complexity in the constraint language against our experience that vocabulary mismatches can quickly be diagnosed by inspecting schema validator outputs, we still decided not to add enumerations of allowed values to the constraint language.…”
Section: Elements As Appropriate)mentioning
confidence: 99%